The effect of usability on satisfaction and its impact on loyalty of BRI mobile users in Bandar Lampung (Asian Journal of Economics and Business Management, 2022)
Internet-based business applications are a manifestation of the path of information technology development that is utilized by financial institutions, especially banking institutions through mobile banking applications. One of the banks that utilize internet technology in serving its customers is PT Bank Rakyat Indonesia (Persero) Tbk. With BRImo is a mobile application that is used by customers and is quite well known by the people of Indonesia, especially in the city of Bandar Lampung, Indonesia. It is necessary to create usability in the BRImo application so that users can feel satisfied with using the BRImo application and continue to be loyal to making BRImo a mobile banking application that is used daily. This study examines the effect of usability to satisfaction and loyalty. Collecting data using a questionnaire and taking a sample of 100 respondents using a purposive sampling technique. Through descriptive statistical analysis tests, outer models, inner models, and hypothesis testing, the data were examined regressively using SmartPLS. The results show that usability has a positive impact on satisfaction and loyalty respectively and there is an indirect effect between usability and loyalty which is mediated by satisfaction. The limitations of this study are the lack of independent variables and the area which only includes the city of Bandar Lampung so further research is expected to be able to add independent variables that allow and conduct research in other areas.